Are humans (higher) animals? On the rational awakening and life transcendence of death cognition - Sherman XIE (Acta Psychologica)
This article delves into the fundamental cognitive question of whether humans are (superior) animals from a utilitarian perspective. Modern biology classifies humans as animals, yet nearly all religious doctrines assert a distinctiveness of humans from animals. Humans, as higher animals, indeed possess a certain degree of rationality and intelligence compared to other lower animals. However, the innate ignorance of humans has not transcended that of lower animals. When it comes to judging the priority, importance, and urgency of their interests, humans, as higher animals, often exhibit a similar narrow-mindedness and short-sightedness as lower animals. This is primarily evident in the fact that most people have no alertness whatsoever to the constant possibility of their own death, and they show a dismissive attitude towards the fundamental metaphysical issues that could help them address the inevitability of death. From a utilitarian perspective, the predominance of human instrumental rationality over value rationality will inevitably lead to ultimate destruction through war and ecological disasters.